Web-based instruction a guide for libraries - Smith, Susan Sharpless (IG library, 2010)
This updated edition of the classic covers new tools and trends, including current browsers, access methods, hardware, and software. Includes tips to secure project funding and provides strategic guidance for all types of libraries.